(untitled) (Eurasian Scientific Herald, 2025)
Neuromarketing covers a wide range of strategies and methods that help to understand and influence consumer behavior, allowing you to determine which products are best sold, which videos will be most effective for advertising, and which method to choose for store shelves, and the article highlights the three elementals of the entire concept of neuromarketing